Estudio preliminar paleolimnológico del Embalse San Roque (Córdoba, Argentina) - Degano, María Florencia; Rodriguez, María Inés; Ruiz, Marcia; Halac, Silvana; Ruibal Conti, Ana Laura; Arán, Daniela; Sada, Carolina; Dasso, Clarita; Piovano, Eduardo (2024)
Fil: Degano, María Florencia. Instituto Nacional del Agua INA-Centro Región Semiárida; Argentina.